16S rRNA gene-based assessment of common broiler chicken sampling methods: Evaluating intra-flock sample size, cecal pair similarity, and cloacal swab similarity to other alimentary tract locations - Weinroth, Margaret D.; Oakley, Brian; Ramírez, Gustavo A.; Reyes, Arquimides; Harris, Caitlin E.; Buhr, R. Jeff (Frontiers in Physiology, 2022)
16S rRNA gene sequencing for characterization of microbiomes has become more common in poultry research and can be used to both answer specific research questions and help inform experimental design choices. The objective of this study was to use 16S rRNA gene sequencing to examine common sampling practices in broiler chicken studies such as: the required number of birds selected from a flock to adequately capture microbiome diversity, the differences between cecal pairs within the same bird, and whether cloacal swabs are representative of other alimentary tract (AT) locations. To do this, nine market age broilers were euthanized and immediately sampled in ten AT locations: crop, gizzard, proventriculus, duodenum, jejunum, ileum, cecal samples from each pouch, colon, and cloacal swab. DNA was extracted and subjected to 16S rRNA gene amplification and sequencing. Each location within the broiler AT hosts distinct microbial communities. When each sampling location was considered, it was found that sampling after 2.8 birds (range 2-4) resulted in less than 10% new amplicon sequencing variants (ASV) being added while sampling after 7.6 birds (range 6-10) increases new observed ASVs by less than 1%. Additionally, when cecal pairs from the same bird were evaluated, it was found that cecal pair mates are an adequate replication if interested in the total cecal microbiome but may be less useful if a rare lineage is of interest. Furthermore, when compared to other AT locations, the cecal microbiome was enriched in Firmicutes and Bacteroides while several lineages, most notably Lactobacillus, were under-represented. Finally, when cloacal swabs were compared to other AT locations, community similarity exhibited a direct distance relationship, i.e.: the more aborad samples were the more similar they were to the swab. These findings indicate that while cloacal swabs can approximate overall changes in microbiome composition, they are not adequate for inferring changes to specific taxa in other parts of the AT tract—even those that are highly abundant within the microbial community. These data provide new insights guiding appropriate sample size selection within flocks and add to the consensus data regarding cecal pair similarity and destructive versus non-destructive sampling methods.